La « continuité pédagogique » : une injonction paradoxale ? Le cas des Instituts Universitaires de Technologie - Aude Seurrat (Centre National d'Enseignement à Distance, 2022)
This article deals with the implementation of « pedagogical continuity » in the French University Institutes of Technology (IUT) during the period from April 2020 to January 2021. It questions more specifically the difficulty or even impossibility to shift some pedagogical activities to remote mode. The methodology articulates a discourse analysis of regional press articles with 13 interviews driven by members of the ANR RENOIR IUT project with IUT teachers during the lockdown period. The cross-analysis allowed to point out polyphony in the « pedagogical continuity » formula. It also raises the question of the relations between educational and digital conceptions. It particularly highlights the fact that digital technology cannot be considered as being in itself an educational innovation. After showing the difficulties that IUTs encounter more specifically in setting up remote education, the article shows how « pedagogical continuity » can be considered as a formula that aims at neutralizing the controversial dimension of this situation.